On desire : why we want what we want - Irvine, William Braxton, 1952- (Oxford University Press, 2006)
Desires often come to us unbidden and unwanted, and they can have a dramatic impact, sometimes changing the course of our lives. Philosopher Irvine takes us on a wide-ranging tour of our impulses, wants, and needs, showing us where these feelings come from and how we can try to rein them in. Irvine considers the teachings of religion as well as ancient and modern philosophers, looks at what modern science can tell us about desire--what happens in the brain when we desire something and how animals evolved particular desires--and advances a new theory about how desire itself evolved. Brimming with wisdom and practical advice, On Desire offers a thoughtful approach to controlling unwanted passions and attaining a more meaningful life.--From publisher description.